522 A strange case of bradycardia in a 38-year-old woman postpartum. (8th December 2021) - Bastianoni, Gianmarco; Paolini, Federico; Stronati, Giulia; Casella, Michela; Antonio, Dello Russo; Guerra, Federico
Abstract: Methods and results: A 38-year-old woman at her 4th day postpartum from a twin pregnancy, presented to the Emergency Room with general malaise, headache, and dyspnoea. Her symptoms had started to show 2 days prior to her ER admission and were worsened by bilateral pitting oedema. In particular they had started when she was administered cabergoline to suppress lactation. Her blood pressure was elevated (160/80 mmHg) and her heart rate was 40 b.p.m. On examination she was oriented in time and space. Her laboratory exams showed anaemia (Hb 8.8 g/dl), with negative D-dimer and troponin. She had no urine proteinuria, which allowed pre-eclampsia to be excluded from the diagnostic hypotheses. A 12-lead ECG was performed and showed junctional rhythm with isorhythmic dissociation at 40 b.p.m. She was admitted to the cardiology ward for diagnostic workup. Her echocardiogram showed no structural alteration and preserved ejection fraction. A cardiac magnetic resonance confirmed the absence of structural alterations or late gadolinium enhancement. During her hospital stay, sinus rhythm was spontaneously restored at 42 b.p.m.; in addition to this, restoration of sinus rhythm, although bradycardic, was associated to the resolution on both her symptoms and of her pitting oedema. She was discharged with a diagnosis of bradycardia secondary to carbegoline use. Her Holter ECG, performed 7 days after discharge, showed sinus bradycardia with occasional isorhythmic dissociation. Conclusions: Cabergoline is an ergot-derived dopamine agonist usually used in the treatment of Parkinson's disease. It acts selectively on D2 receptors. It can be associated to orthostatic hypotension, cardiac valvular fibrosis, and angina pectoris. No cases of cabergoline-induced bradycardia can be currently found in literature; however, a similar effect was seen with the use of methylergometrine in a women during her post-partum period. Furthermore, studies on mice have shown that ergot derivatives may cause reduction of heart rate. It therefore seems possible that in our case, the use of cabergoline induced the patient's bradyarrhythmia.